Optimal Colostomy Placement in Spinal Cord Injury Patients. Issue 3 (March 2016) - Xu, Jiashou; Dharmarajan, Sekhar; Johnson, Frank E.
Barring unusual circumstances, sigmoid colostomy is the optimal technique for management of defecation in spinal cord injury (SCI) patients. We sought to provide evidence that a sigmoid colostomy is not difficult to perform in SCI patients and has better long-term results. The St. Louis Department of Veterans Affairs has a Commission on Accreditation of Rehabilitation Facilities (CARF)–approved SCI Unit. We reviewed the operative notes on all SCI patients who received a colostomy for fecal management by three ASCRS-certified colorectal surgeons at the St. Louis Department of Veterans Affairs from January 1, 2007 to November 26, 2012. There were 27 operations for which the recorded indication for surgery suggested that the primary disorder was SCI. Fourteen had traumatic SCI of the thoracic and/or lumbar spine and were evaluable. Of these 14 patients, 12 had laparoscopic sigmoid colostomy and two had open sigmoid colostomy. We encountered one evaluable patient with a remarkably large amount of retroperitoneal bony debris who successfully underwent laparoscopic sigmoid colostomy. In conclusion, sigmoid colostomy is the consensus optimal procedure for fecal management in SCI patients. Laparoscopic procedures are preferred. Care providers should specify sigmoid colostomy when contacting a surgeon.